Screening of some isoxazole derivatives as plausible inhibitors of E. coli: a computational and synthetic approach - Judy Jays; Saravanan Janardhanan (Discover Chemistry)
Abstract Novel isoxazole-based analogues were rationally designed and subjected to virtual screening via in-silico methodologies, with the objective of identifying potential anti-Escherichia coli agents targeting key enzymes implicated in the microorganism’s metabolism and proliferation. Molecular docking analyses were conducted to evaluate the binding affinity and specificity of these analogues toward critical E. coli enzymes: dihydrofolate reductase, enoyl-[acyl-carrier-protein] reductase (FabI), DNA gyrase, and methionine aminopeptidase. To assess their drug-likeness, in-silico ADME (absorption, distribution, metabolism, and excretion) profiling was performed, with the results suggesting favourable pharmacokinetic properties. Lead compounds identified through virtual screening were subsequently synthesized and structurally characterized using various spectroscopic techniques including NMR and HR-MS. These analogues were then evaluated for their in vitro antibacterial efficacy. Notably, compounds 2c and 2d, featuring hydroxyl substitutions at positions 2 and 4 respectively, exhibited significant inhibitory activity against the tested E. coli strain. The observed bioactivity is hypothesized to result from the inhibition of enoyl reductase, as both derivatives exhibited strong binding affinities and stable interactions within the enzyme’s active site. The activity may be attributed to the presence of hydroxyl groups, which facilitate hydrogen bonding with active site residues of the target enzyme. These findings suggest that compounds 2c and 2d represent promising leads for the development of novel enoyl reductase targeted antibacterials, underscoring their potential for further structural optimization toward development of effective anti-E. coli therapeutics.